Eupatorium herbicide treatment - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Although the Eupatorium weed, found throughout most African forests, quickly invades clearings it poses few problems to established oil palm plantations because its growth is slow under shady conditions. However once the palm trees are cut down,...